Pengembangan Sistem Informasi Manajemen Service Motor pada Bengkel Honda Putra Jaya Malang - Firhan Fauzan Hamdani; Adam Hendra Brata; Novanto Yudistira (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
PT Astra Honda Motor as a manufacturer of Honda motorcycles has many interrelated activities, one of the most important aspects is after sales service. After-sales service is a form of responsibility of PT Astra Honda. Putra Jaya Malang Motorbike Workshop is a Honda authorized workshop and dealer company engaged in motorcycle service. Service transactions, customer receipts, motorcycle history records and inventory records available and sold in the form of motorcycle parts are still done manually. Based on the problems that occur, it is necessary to develop a system of motor service management information in the workshop. This research uses the waterfall method in the development of information systems and uses the PHP programming language that is implemented in codeigniter frame-work. This information system has been tested using themethod blackbox for validation testing that produces 20 (twenty) test cases with 100% valid results, themethod whitebox for unit testing and compatibility testing for testing non-functional requirements on 3 (three) webs abrowser differentwith the results of the system running well.